HERMENEUTICAL TRUTH AND AUTHORIAL INTENTION: MODERN PROJECTS - BONDOR, George (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
The aim of this text is to reconstruct the meanings of the concept of hermeneutical truth, as it has been defined and explained in the main projects of modern hermeneutics (Dannhauer, Chladenius, Meier, Schleiermacher, Fr. Schlegel). I will explore the epistemological side of this concept, different from its meaning in hermeneutic ontology. Understood as correctness by modern hermeneutics, truth has been related to the authorial intention. The thesis I am arguing is that the meanings of hermeneutical truth and, related to them, the modern theories of authorial intention differ according to the metaphysical presuppositions that define the thought paradigms of modernity (Cartesianism, Kantianism, Romanticism and German Idealism): the centrality and activism of the self, the rationality of the self, the dependence of knowledge on the ideal of method, the discovery of the unconscious. Some modern hermeneutical theories express the tensions between these philosophical paradigms. However, I will argue that the authorial intention remains a limit of interpretation that prevents the risks of arbitrariness and hermeneutic relativism. Translated by Mariana Constantinescu